Implantação de metodologia ágil de projetos com uso de Scrum e Kanban na produção de conteúdos educacionais - Fontes, Marcelo Henrique Ferreira (2020)
In the current management model adopted by FTD Educação, a provider of educational solutions, there is a frequent delay in the delivery of educational content in time for the school service campaign to begin, resulting on the presentation of incomplete educational solutions that hinder the commercialization process. In this context, the objective of this project was to understand, investigate and diagnose potential causes of delays to propose an applicable solution to the company to eliminate the problem. Questionnaires were prepared and applied to the company's managers, and the results revealed a lack of project management methodologies aimed at creative and collaborative products. The lack of methodology forces editorial managers to adopt inefficient processes and systems for coordinating simultaneous projects, which results in production delays and non-compliance with deadlines. To solve the problem, this work proposes the adoption of two agile methodologies (Scrum and Kanban) with sufficient flexibility and adaptability to be applied on FTD Educação's editorial manufacturing. Scrum is a framework for improving the production process and Kanban is a technique that allows better workflow visualization. The adoption of these methodologies by FTD Educação represents an innovation that contemplates cultural and operational changes that involves all organizational levels and will introduce innovations to the production process, like the new work format for the editorial team. As this is a complex change that involves a significant number of employees and possible impacts on the company's operation, this work proposes the adoption of suggested methodologies in two phases. In the first stage there is the execution of a pilot project to assess the real feasibility and effectiveness of the proposal in solving the problem. The second phase considers the evaluation of the results observed in the pilot project to ascertain the need for adjustments and improvements on the Scrum framework and Kanban board for posterior application in other editorial managements. The predicted impact with the adoption of the suggested methodologies is the production of innovative educational content and continuous support to the company's mission of contributing to society through modern and quality educational solutions, helping children and young people to learn.